2009
DOI: 10.1002/ceat.200900275
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mass Transfer Coefficients in Biotrickling Filters: Experimental Determination and Comparison to Correlations

Abstract: Overall mass transfer coefficients (K G a and K L a) were determined experimentally for four different-nature packing materials used in gas-phase biotrickling filters. A simple methodology based on overall mass balances and following a standard procedure allowed to calculate the mass transfer coefficients under different operating conditions corresponding to usual biotrickling filtration situations. Results showed an increase of mass transfer resistance when increasing the empty bed residence time (EBRT) of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 19 publications
6
29
0
Order By: Relevance
“…Mass transfer coefficients increased exponentially when decreasing the EBRT from 241 ± 38 h −1 at 94 s to 697 ± 40 h −1 at 32 s. These k L a values are quite high compared to those reported by Dorado et al [20] in a biotrickling filter packed with polyurethane foam at 35 s of EBRT (k L a ≈ 43.2 h −1 ). However, the k L a increased up to 700 h −1 when the EBRT of the biotrickling filter decreased to 10 s.…”
Section: Resultssupporting
confidence: 49%
“…Mass transfer coefficients increased exponentially when decreasing the EBRT from 241 ± 38 h −1 at 94 s to 697 ± 40 h −1 at 32 s. These k L a values are quite high compared to those reported by Dorado et al [20] in a biotrickling filter packed with polyurethane foam at 35 s of EBRT (k L a ≈ 43.2 h −1 ). However, the k L a increased up to 700 h −1 when the EBRT of the biotrickling filter decreased to 10 s.…”
Section: Resultssupporting
confidence: 49%
“…The glass fibre BTF was packed with inert plastic supports, which exhibited a density of 100 kg m À3 and a total pressure drop of 500 Pa (Dorado et al, 2009). In the first stage, the pH was maintained at 2 for the efficient removal of H 2 S and in a second stage a neutral pH was kept to favour the removal of the other odorants.…”
Section: Biotrickling Filter (Btf)mentioning
confidence: 99%
“…They included suggestions from Hoffmann et al (2007) to minimize most common errors found in mass transfer studies. Dorado et al (2009) pointed out that in typically used biological gas treatment systems (biofilter and biotrickling filters), the gas phase resistance should not be neglected at high gas contact times (low gas velocities), probably because diffusion in the gas phase is the dominant process rather than advection.…”
Section: Determining Mass Transfer Ratesmentioning
confidence: 99%